SIGNIFIKANSI DAMPAK PEMILU 2024 INDONESIATERHADAP PERTUMBUHAN EKONOMI - Deddy Ahmad Fajar; Dian Mafulla; Farah Nur Fauziah (El-Idaarah, 2022)
The aim of this research is to see the impact of elections on Indonesia'seconomic growth. Descriptive event study research which tests whether ornot there is a market reaction due to an event, as well as secondary data fromvarious references, the research results come from data that has beenprocessed by previous researchers. The research results show that the 2024election will not reduce Indonesia's economic growth but will tend toincrease economic growth. This is due to the encouragement of electionspending and investor confidence in the conduciveness of Indonesia'seconomic growth.